2005
DOI: 10.1007/s11908-005-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

An approach to oral infections and their management

Abstract: Oral infections can be odontogenic or nonodontogenic in origin. Odontogenic infections are most prevalent and include dental caries, periodontal disease, and suppurative deep space infections. Nonodontogenic infections include sialadenitis and parotitis, vesiculobullous gingivostomatitis, aphthous ulcers, oropharyngeal candidiasis, and severe oral mucositis in the immunocompromised host. Clinical presentations can be variable. An understanding of the underlying anatomic structures, the oral microflora, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
(45 reference statements)
0
14
0
1
Order By: Relevance
“…Looking beyond individual management, the cumulative 1326 antibiotic days of treatment amongst the 110 participants in this study represents excessive exposure for a condition that is preventable and for which primary management entails dental intervention [9, 10, 25]. Despite little evidence supporting antibiotic therapy as management of most types of dental infections – a recent systematic review on the topic concluded the quality of available evidence is “very low” [26] - it is estimated that 8 to10% of all primary care antibiotic prescriptions are for treatment of dental infections [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking beyond individual management, the cumulative 1326 antibiotic days of treatment amongst the 110 participants in this study represents excessive exposure for a condition that is preventable and for which primary management entails dental intervention [9, 10, 25]. Despite little evidence supporting antibiotic therapy as management of most types of dental infections – a recent systematic review on the topic concluded the quality of available evidence is “very low” [26] - it is estimated that 8 to10% of all primary care antibiotic prescriptions are for treatment of dental infections [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive management of ADI requires dental intervention; generally tooth extraction or root canal treatment, and often hospitalization. Antibiotics may serve a limited temporizing role pre- and peri-intervention but are not definitive management alone [9, 10]. Between 2000 and 2008 ADI hospitalization in the United States increased by 41%, after adjustment for growth, resulting in 8191 admissions in 2008 with attributed healthcare costs exceeding $105 million [2, 11].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] Typical causative agents of mandibular osteomyelitis are those of the normal oral flora as well as bacteria known to cause dental caries and periodontal diseases. 7 Fungal causes of mandibular osteomyelitis are rare, and those caused by Blastomyces are not welldescribed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Hull 16 and Holmstrup 17 demonstrated that the oral cavity is the main route of entry of etiological agents in infectious endocarditis.…”
Section: Discussionmentioning
confidence: 99%